ANTECEDENT AND CONSEQUENCES OF CUSTOMER SATISFACTION OF LOCAL FAST FOOD IN INDONESIA - Yonatan Stenly Sugiarto; Luki Adiati Pratomo (Manajemen: Jurnal Ekonomi, 2024)
The aim of this research is to analyze the positive influence of customization, entertainment, trendiness, interaction on purchase intention, the positive influence of customization, entertainment, trendiness, interaction on customer satisfaction, consumer satisfaction on purchase intention. The data analysis method in this research applies the structural equation model (SEM), is a powerful multivariate tool for analyzing research hypotheses via AMOS ver 23. The expected results in this research are concluded as follows: Customization has a positive effect on purchase intention, Entertainment has a positive effect on purchase intention, There is no positive effect of trendiness on purchase intention, There is no positive effect of interaction on purchase intention, Customization has a positive effect on customer satisfaction, Entertainment has an effect positive effect on customer satisfaction, Trendiness has a positive effect on customer satisfaction, There is no positive effect of interaction on customer satisfaction, Customer satisfaction has a positive effect on purchase intention. This research can provide input and recommendations for further research by adding independent variables, namely food quality and physical environment quality, then it would be better to add other local fast food in Indonesia